Correlates of lifestyle patterns among children in Singapore aged 10 years: the Growing Up in Singapore Towards healthy Outcomes (GUSTO) study - Sarah Yi Xuan Tan; Airu Chia; Bee Choo Tai; Jia Ying Toh; Marjorelee Colega; Natarajan Padmapriya; Peipei Setoh; Michelle Zhi Ling Kee; Wen Lun Yuan; Yung Seng Lee; Benny Kai Guo Loo; Fabian Kok Peng Yap; et al. (BMC Public Health, 2024)
Abstract Objective To characterise lifestyle patterns (comprising dietary and movement behaviour aspects) of children in Singapore and examine the correlates of these patterns. Design An observational study approach was used. Children recorded their diet and activities over two weekdays and two weekend days on a validated web-based assessment, My E-Diary for Activities and Lifestyle (MEDAL). Lifestyle patterns were derived using principal component analysis, and the correlations of these with multiple known determinants organised by distal, intermediate, and proximal levels of influence were studied. Setting Children of the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort. Participants Ten-year-old children (n = 397). Results Three lifestyle patterns, “high snacks and processed food”, “balanced” and “mixed”, were identified. We focused on the more health-promoting “balanced” pattern, characterised by lower screen-viewing and higher consumption of fruits, vegetables, wholegrains, and dairy. Among the distal factors, girls were more adherent to the “balanced” pattern compared to boys, and children of parents with lower education levels were less adherent to this pattern. Among intermediate factors, children of mothers with higher diet quality were more adherent to the “balanced” pattern. Among the proximal factors, engagement in active transport, leisure sports, and educational activities outside of school were positively associated with the “balanced” pattern, whereas screen-viewing while travelling was negatively associated with this pattern. Having siblings, pet ownership, mother’s physical activity, parenting style, parental bonding, child’s outdoor time, and breakfast consumption were not associated with children’s lifestyle patterns. Conclusions These findings provide direction for future interventions by identifying vulnerable groups and contexts that should be prioritised.